1999
DOI: 10.1562/0031-8655(1999)069<0617:trsote>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Studies of the Excited-State Dynamics of meso-Tetra(hydroxylphenyl)chlorin in Solution

Abstract: Meso-tetra(hydroxyphenyl)chlorin (m-THPC) is a new photosensitizer developed for potential use in photodynamic therapy (PDT) for cancer treatment. In PDT, the accepted mechanism of tumor destruction involves the formation of excited singlet oxygen via intermolecular energy transfer from the excited triplet-state dye to the ground triplet-state oxygen. Femtosecond transient absorption measurements are reported here for the excited singlet state dynamics of m-THPC in solution. The observed early time kinetics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…The analogous data for ALA-PpIX were reported previously in Jarvi et al (12), but the rate constants were not determined and so are also now included in Table 2. The results are in good agreement with published values of k OT for mTHPC and porphyrin-based photosensitizers (27,28), which lie in the range 1.4-2.7 · 10 9 M M )1 s )1 . In order to model the in vitro kinetics, it was necessary to determine the changes in [ 3 O 2 ] that are due to metabolic rather than photochemical consumption.…”
Section: Resultssupporting
confidence: 90%
“…The analogous data for ALA-PpIX were reported previously in Jarvi et al (12), but the rate constants were not determined and so are also now included in Table 2. The results are in good agreement with published values of k OT for mTHPC and porphyrin-based photosensitizers (27,28), which lie in the range 1.4-2.7 · 10 9 M M )1 s )1 . In order to model the in vitro kinetics, it was necessary to determine the changes in [ 3 O 2 ] that are due to metabolic rather than photochemical consumption.…”
Section: Resultssupporting
confidence: 90%
“…It is reported that the excited state for mTHPC in solution has an apparent triplet state life time of ca 250 ns in air . The triplet state life time for hypericin was found to be 370 ns .…”
Section: Discussionmentioning
confidence: 99%
“…16 From time-resolved fluorescence measurements in ethanol the lifetime of the lowest vibrational state of S 1 was assigned to 10 ns. 17 Using the LDH-C 400 for excitation, we observed a decrease in the fluorescence lifetime from 7.5 to 5.5 ns in the cytoplasm of cells during increasing incubation time. The different results To prove the results from time-resolved spectroscopy, the fluorescence lifetime of mTHPC was alternatively determined by TCSPC.…”
Section: Discussionmentioning
confidence: 99%